Withania coagulans Dunal: A Review - Hemalatha, S.; Kumar, Rajesh; Kumar, Manish (Pharmacognosy Reviews)
The withania coagulans belonging to family Solonaceae and distributed mainly in East of the Mediterranean region, extending to South Asia. This plant is rich in withanolide. The Withania coagulans possess a number of medicinally important activities such as antifungal activity, anthelmintic, antimicrobial, hypolipidemic, antioxidant, anti-cytotoxic, anti-fungal activity, Hypoglycemic activity etc. Fruits of Withania coagulans gaining popularity as a antidiabetic. The present review explores its economical importance, distribution, chemical composition, pharmacological activity and traditional uses of Withania coagulans.
Keywords: Antidiabetic; hypolipidemic; wound healing; anti- inflammatory; Withania coagulans; Withanolide